Clinical presentation and prognosis of adenosquamous carcinoma of the pancreas: matched-pair analysis with pancreatic ductal adenocarcinoma - Kaiser, Jörg; Hinz, Ulf; Mayer, Philipp; Hank, Thomas; Niesen, Willem; Hackert, Thilo; Gaida, Matthias; Büchler, Markus W.; Strobel, Oliver (European journal of surgical oncology, 2021)
Introduction - Adenosquamous carcinoma of the pancreas (ASCP) is a rare subtype of pancreatic adenocarcinoma. The aim of this study was to investigate the characteristics and outcomes of ASCP in comparison to pancreatic ductal adenocarcinoma (PDAC). - Materials and methods - All patients with ASCP treated between December 2001 and December 2017 were identified from a prospective database. Clinicopathological and follow-up data were analyzed. A nested case-control-study with matched-pair analysis was performed to compare overall survival of ASCP and PDAC. - Results - Of 4009 patients undergoing surgery for pancreatic adenocarcinoma 91 patients had ASCP. Compared to PDAC ASCP were larger (4.0 vs. 3.2 cm; p < 0.0001), more frequently involved lymph nodes (88% vs. 78%; p = 0.0216), more frequently showed poor differentiation (G3: 79% vs. 36%; p < 0.0001) and more frequently were located in the pancreatic tail (19% vs. 10%; p = 0.0179). Overall median post-resection-survival was shorter in ASCP (10.8 vs. 20.5 months in PDAC; p = 0.0085), but 5-year survival rates were comparable (18.2% vs. 17.5%). After matching for the unevenly distributed prognostic factors survival after resection of ASCP and PDAC was comparable (p = 0.8301). Localization in the head or several parts of the pancreas, high CA 19-9 levels, and M1 disease were independent predictors of survival in patients with ASCP. - Conclusion - ASCP is more aggressive with poorer differentiation and higher rates of lymph node metastases compared to PDAC. In spite of a shorter median survival, 5-year survival rates after surgical resection of about 18% can be expected in ASCP and support resection as part of a multimodal therapy as the treatment of choice in this rare cancer.
Gesehen am 14.07.2021